Distribusi Coulomb Stress Akibat Gempabumi Tektonik Selatan Pulau Jawa berdasarkan Data Gempa Tektonik 1977-2000: Fitri Puspasari, Wahyudi - Fitri Puspasari Fitri Puspasari; Wahyudi Wahyudi (Jurnal Fisika dan Aplikasinya, 2017)
This study has been applied to calculate Coulomb stress distribution using Coulomb 3.3 software. Increasing the value of Coulomb stress changes indicated accumulation of stress on rocks. The data is taken from the catalog of ISC (International Seismological Center) and Global CMT (Global Centroid Moment Tensor). The results of data processing is an increase in Coulomb stress in the South of Java Island with a ranges 0.01-1 kPa and allegedly caused the accumulation of stress due to tectonic earthquake that leads to the volcano.